Acetone as a greener alternative to acetonitrile in liquid chromatographic fingerprinting. Issue 9 (2nd April 2015) - Funari, Cristiano Soleo; Carneiro, Renato Lajarim; Khandagale, Manish M.; Cavalheiro, Alberto José; Hilder, Emily F.
<x xml:space="preserve">Abstract</x> A considerable amount of chemical waste from liquid chromatography analysis is generated worldwide. Acetonitrile is the most employed solvent in liquid chromatography analyses since it exhibits favorable physicochemical properties for separation and detection, but it is an unwelcome solvent from an environmental point of view. Acetone might be a much greener alternative to replace acetonitrile in reversed‐phase liquid chromatography, since both share similar physicochemical properties, but its applicability with ultraviolet absorbance‐based detectors is limited. In this work, a reference method using acetonitrile and high‐performance liquid chromatography coupled to an ultraviolet photodiode array detector coupled to a corona charged aerosol detector system was developed to fingerprint a complex sample. The possibility of effectively substituting acetonitrile with acetone was investigated. Design of experiments was adopted to maximize the number of peaks acquired in both fingerprint developments. The methods with acetonitrile or acetone were successfully optimized and proved to be statistically similar when only the number of peaks or peak capacity was taken into consideration. However, the superiority of the latter was evidenced when parameters of separation and those related to greenness were heuristically combined. A green, comprehensive, time‐ and resource‐saving approach is presented here, which is generic and applicable to other complex matrices. Furthermore, it is in line with environmental legislation and analytical trends.